Solidarity and individualism in an archipelago state : a Bahamian cultural model in historical context - Brown, Susan Love (2005)
Presents a model of solidarity and individualism as seen in the operation of the customary land tenure system, and how this model is extended to other domains of Cat Island life. Examines the cultural and historical origins and parallel development of solidarity and instrumental individualism of Cat Island and the Bahamas.